2016
DOI: 10.1161/circimaging.115.004148
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Hemorrhage After Acute Reperfused ST-Segment–Elevation Myocardial Infarction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
175
3
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 177 publications
(216 citation statements)
references
References 47 publications
7
175
3
13
Order By: Relevance
“…14 The breakdown products of hemoglobin within the myocardium can be detected as a hypo-intense core 39 within the MI zone on T2*-imaging or T2*-mapping (Figures 1 and 2). Of the two approaches, T2*-mapping has been shown to have greater sensitivity for detecting intramyocardial hemorrhage following STEMI when compared to T2-mapping (Table 1).…”
Section: Basic Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 The breakdown products of hemoglobin within the myocardium can be detected as a hypo-intense core 39 within the MI zone on T2*-imaging or T2*-mapping (Figures 1 and 2). Of the two approaches, T2*-mapping has been shown to have greater sensitivity for detecting intramyocardial hemorrhage following STEMI when compared to T2-mapping (Table 1).…”
Section: Basic Conceptsmentioning
confidence: 99%
“…The extent of late microvascular obstruction has been reported to peak at 4–12 hours, to remain stable the first 2 days and to reduce in size by day 10 following STEMI. 14 Furthermore, in those patients with microvascular obstruction persisting at one week, Orn and colleagues 49 showed that they were more likely to develop adverse LV remodeling compared to those with microvascular obstruction at day 2 only. On the other hand, the detection of intramyocardial hemorrhage has been shown to peak at day 3, and to reduce in incidence by day 10 following PPCI.…”
Section: Recent Advances In the Role Of Cmr In Reperfused Stemi Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, failed myocardial reperfusion, depicted by microvascular obstruction on contrast‐enhanced cardiac magnetic resonance (CMR) imaging, occurs in more than half of these patients,3, 4 implicating an adverse long‐term prognosis 5, 6…”
mentioning
confidence: 99%
“…Standard measures of myocardial reperfusion, including TIMI (Thrombolysis in Myocardial Infarction) Myocardial Perfusion Grade and corrected frame count, or ST‐segment resolution on the ECG, lack sensitivity and reproducibility 6, 7, 8, 9. CMR is the reference noninvasive technique for detection of microvascular pathology3, 5, 10; however, CMR is neither feasible acutely nor widely available1 and is not routinely recommended in contemporary practice guidelines 1, 11…”
mentioning
confidence: 99%